Persepsi Wisatawan, Pelancong, Dan Masyarakat Lokal Terhadap Sistem Transportasi Umum Di Destinasi Wisata Pantai Kuta - I Gede Adi Wika Darmawan; I Putu Anom (JURNAL DESTINASI PARIWISATA, 2018)
Kuta Beach is known as tourist favourite attraction in Bali, it can be seen by the number of tourists visited Kuta Beach. However, the high level of tourists, travelers and local communities to Kuta Beach who use private vehicles create traffic jam at Kuta Beach. In this study aims to determine the perception of tourists, travelers and local communities if the implementation of public transport as a special means to Kuta Beach to reduce congestion caused by private vehicles. The research methodology used is quantitative method. With the technique of determining the number of samples using random sampling and quota sampling. In collecting the data using techniques study literature, observation, interviews, documentation, and distribution of the questionnaire to the 40 respondents. In a data analysis technique used descriptive qualitative method by utilizing the percentage of data. The results show the perception of tourists, travelers and local communities towards the implementation of transportation common in Kuta Beach, which answered agree as many as 16 people (40%) strongly agree 15 people (37.5%), undecided 5 people (12.5%), not agree 4 people (10%), strongly disagree 0 (0%). Thus the total percentage of the perception of tourists, travelers and local communities can be seen in the implementation of public transport in the Kuta Beach, the majority of local people answered agree but local communities said the hesitation and do not agree that the implementation of the proposal. Keywords : Kuta Beach, Perception, Tourists, Travelers, Local Communities, Public Transportation.